Librarian E-Readiness in the Disruption 4.0 Era - Surya Adi Sasmita (IKOMIK: Jurnal Ilmu Komunikasi dan Informasi, 2021)
In the era of disruption of the industrial revolution 4.0 as it is today, there are almost no difficulties in meeting information needs. Both information that is educational or information that is entertainment. A librarian is a profession whose job is to provide and present information to its users. how is the level of readiness of higher education librarians in the era of disruption including what factors affect the readiness of librarians and how librarians adjust to the era of disruption 4.0. In this study using the method of Quantitative Research. This method was chosen by the author because the author wanted to know the level of readiness to implement the development of information technology with the basis or tools on the model developed by Mutula and Brakel. E Readiness, shows a value of 3.393. The value can mean “Ready”. This average calculation is obtained from the average results for each sub-indicator which then becomes the value for each segment or indicator and then is averaged again to find the value of readiness information for the era of disruption 4.0. Pada era disrupsi revolusi industri 4.0 seperti saat ini, hampir tidak ada kesulitan dalam hal pemenuhan kebutuhan informasi. Baik informasi yang bersifat pendidikan ataupun informasi yang bersifat hiburan. Pustakawan salah satu profesi yang bertugas menyediakan dan menyajikan informasi bagi penggunanya. bagaimana tingkat kesiapan pustakawan peguruan tinggi dalam era disrupsi termasuk faktor apa saja yang mempengaruhi kesiapan dari pustakawan dan bagaimana pustakawan dalam menyesuaikan diri dalam era disrupsi 4.0. Dalam penelitian ini menggunakan metode Quantitative Research. Metode ini dipilih penulis karena penulis ingin mengetahui tingkat kesiapan implementasi perkembangan teknologi informasi dengan dasar atau tool pada model yang dikembangkan mutula dan brakel. E Readiness, menunjukan nilai 3,393. Nilai tersebut dapat berarti “Siap”. Perhitungan rata – rata ini didapatkan dari hasil rata – rata pada setiap sub indikator yang kemudian menjadi nilai pada setiap segmen atau indikator dan kemudian di rata – rata kembali untuk menemukan nilai keterangan kesiapan terhadap era disrupsi 4.0.